Socialization of the Impact of Thuggery in Hindering Investment and the Progress of Rural MSMEs: Penelitian - Herni Ramayanti; Heri Fitriadi; Darwin Kesuma; M. Pahlan; Samuel Indrayana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article is a compilation of the author's outreach to fellow lecturers regarding tips on how to avoid predatory journals. The lecturers involved in this outreach came from several universities especially Muhammadiyah University of Makassar Indonesia, Doktor Nugroho University of Magetan Indonesia, Doktor Nugroho University of Magetan Indonesia and Antasari State Islamic University of Banjarmasin Indonesia. The author sincerely hopes that after this outreach, all lecturers targeted in this article will be able to choose higher-quality journals and avoid predatory journals, which have the various characteristics explicitly and comprehensively outlined above. By avoiding predatory journals, the author believes the quality of lecturers' research will continue to improve in the coming periods.